Faktor Risiko Cemaran Biologis Air Sumur Gali Di Kelurahan Tamangapa Kota Makassar - Haerani Haerani; Andi Ruhban; Rahmat Hidayat (Direktorat Politeknik Kesehatan Makassar, 2024)
Dug well water is one of the primary sources of clean water for the community but is often vulnerable to bacteriological contamination, such as MPN Coliform. This contamination can cause various diseases, including diarrhea, particularly if the well is too close to contamination sources, the physical structure of the well does not meet standards, or the well owner's hygiene behavior is poor. This study aims to analyze the risk factors associated with the presence of MPN Coliform in dug well water in Tamangapa Village, Makassar City. The research used a cross-sectional design with purposive sampling of 12 dug wells, analyzed using Fisher's exact test. The results showed a significant relationship between the distance from contamination sources (SPAL, livestock pens, and septic tanks) and the presence of MPN Coliform in dug well water, with a p-value of 0.028 < 0.05 (odds ratio = 3.5). There was no relationship between the behavior of well owners (storage of well buckets, bathing, and washing) or the structure of dug wells (well walls and floors) and the presence of MPN Coliform, with p-values > 0.05. This study concludes that the distance of wells from contamination sources is the primary risk factor in determining the bacteriological quality of dug well water. Therefore, efforts are needed to maintain a safe distance between wells and contamination sources to reduce the risk of contamination. It is recommended that the community increase awareness of well sanitation and hygienic behavior, while the government strengthens the monitoring of well water quality. Keywords: Water; MPN Coliform; Dug Wells